Mantle dynamics of the Andean Subduction Zone from continent-scale teleseismic S-wave tomography - Rodríguez, Emily E. (2021)
The Andean Subduction Zone is one of the longest continuous subduction zones on Earth. The relative simplicity of the two-plate system has makes it an ideal natural laboratory to study the dynamics in subduction zones. We measure teleseismic S and SKS traveltime residuals at >1000 seismic stations that have been deployed across South America over the last 30 yr to produce a finite-frequency teleseismic S-wave tomography model of the mantle beneath the Andean Subduction Zone related to the Nazca Plate, spanning from ~5°N to 45°S and from depths of ~130 to 1200 km. Within our model, the subducted Nazca slab is imaged as a fast velocity seismic anomaly. The geometry and amplitude of the Nazca slab anomaly varies along the margin while the slab anomaly continues into the lower mantle along the entirety of the subduction margin. Beneath northern Brazil, the Nazca slab appears to stagnate at ~1000 km depth and extend eastward subhorizontally for >2000 km. South of 25°S the slab anomaly in the lower mantle extends offshore of eastern Argentina, hence we do not image if a similar stagnation occurs. We image several distinct features surrounding the slab including two vertically oriented slow seismic velocity anomalies: one beneath the Peruvian flat slab and the other beneath the Paraná Basin of Brazil. The presence of the latter anomaly directly adjacent to the stagnant Nazca slab suggests that the plume, known as the Paraná Plume, may be a focused upwelling formed in response to slab stagnation in the lower mantle. Additionally, we image a high amplitude fast seismic velocity anomaly beneath the Chile trench at the latitude of the Sierras Pampeanas which extends from ~400 to ~1000 km depth. This anomaly may be the remnants of an older, detached slab, however its relationship with the Nazca-South America subduction zone remains enigmatic.